« A good place to throw ashes to the wind » : « Revenir du pays des morts » ou les soubresauts de la pensée dans Percival Everett by Virgil Russell, de Percival Everett. - Sylvie Bauer (Transatlantica)
The aim of this paper is to analyze the way literature and philosophy are, to use the words of Pierre Macheray, “inextricably intertwined” in Percival Everett’s latest novel, Percival Everett by Virgil Russell. In this fragmentary work, different voices collide, never reaching an agreement, be it narrative or theoretical. The result is a form of “convulsive” writing, as Deleuze would have it, pushing language towards its limits and raising the question of meaning.